Cost-effective baby corn (Zea mays) cultivation under drip fertigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2014)
Field experiment was conducted during 2010-2011 at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi, India to study the economic viability of baby corn (Zea mays L.) cultivation round the year (October-February, April-July and August-November) under fertigation system. The present study consisted of nine treatments which includes three fertigation frequencies (biweekly, weekly and fortnightly) and three dripper 0.5, 1.0 and 1.5 kg/cm2 system operating pressures. Yield attributes of baby corn were significantly (P